Relationship Between Age and Education on The Use of 3 Months KB Injection at BPM Sargiatik in 2021 - Susi Amenta Beru Perangin Angin; Mastiur Julianti Butar Butar; Esther Siringo-ringo; Indah Yani Tambunan (Pena Cendekia Insani, 2022)
The research design used is an analytical study with a cross sectional study approach, aiming to determine the relationship between age and education on the use of 3-month injectable family planning at BPM Sargiatik in 2021. The number of samples in this study was 34 people. With accidental sampling technique. Data collection instrument in the form of a questionnaire used to obtain chi square data. The results of this study indicate that there is a relationship between age and using 3-month injections, p value = 0.013. There is a relationship between education using 3-month injection KB with p value = 0.009. It is hoped that health workers will provide more active counseling about 3-month family planning injections to family planning acceptors.